Airway injury during high-level exercise - Kippelen, P.; Anderson, S. D. (British Journal of Sports Medicine, 2012)
Airway epithelial cells act as a physical barrier against environmental toxins and injury, and modulate inflammation and the immune response. As such, maintenance of their integrity is critical. Evidence is accumulating to suggest that exercise can cause injury to the airway epithelium. This seems the case particularly for competitive athletes performing high-level exercise, or when exercise takes place in extreme environmental conditions such as in cold dry air or in polluted air. Dehydration of the small airways and increased forces exerted on to the airway surface during severe hyperpnoea are thought to be key factors in determining the occurrence of injury of the airway epithelium. The injury-repair process of the airway epithelium may contribute to the development of the bronchial hyper-responsiveness that is documented in many elite athletes.